2017
DOI: 10.1167/iovs.17-22155
|View full text |Cite
|
Sign up to set email alerts
|

Incomitance and Eye Dominance in Intermittent Exotropia

Abstract: PurposeTo determine if the deviation angle changes in subjects with intermittent exotropia as they alternate fixation between the right and left eye in primary gaze.MethodsIn this prospective observational cohort study, 37 subjects with intermittent exotropia were tested for evidence of incomitance. The position of each eye was recorded with a video tracker during fixation on a small central target. A cover–uncover test was performed by occluding one eye with a shutter that passed infrared light, allowing cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Overlap in the 95% CIs indicates that the left exotropia was not significantly different from the right exotropia, as in most patients with intermittent exotropia. 22 While this patient was viewing the central target with both eyes, he experienced eight episodes of spontaneous left exotropia. These episodes of spontaneous exotropia were similar to those induced by shutter occlusion (compare the light and dark blue traces in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlap in the 95% CIs indicates that the left exotropia was not significantly different from the right exotropia, as in most patients with intermittent exotropia. 22 While this patient was viewing the central target with both eyes, he experienced eight episodes of spontaneous left exotropia. These episodes of spontaneous exotropia were similar to those induced by shutter occlusion (compare the light and dark blue traces in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overlap in the 95% CIs indicates that the left exotropia was not significantly different from the right exotropia, as in most patients with intermittent exotropia. 22 …”
Section: Resultsmentioning
confidence: 99%
“…We also believe the difference in high spatial frequency cutoff is perhaps not so relevant in our testing because the visual stimulus was a bright LED against a dark background. Moreover, studies in humans by Economides and colleagues 32 , 33 have shown that a strong preference for fixation of the central cross does not influence the choice of eye used to acquire eccentric visual targets. Future testing of fixation preference using near-threshold stimuli could be used to investigate this issue further and test the framework more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that surgical intervention decisions should be made more by the reference of a patient’s suppression depth rather than divergent degree alone, especially for children whose visual function is still developing. Normally, longer duration of deviation results in stronger visual suppression in patients with strabismus ( Adams et al, 2017 ; Cadet et al, 2018 ). However, the situation is much more complicated in IXT patients, as their visual suppression condition is unstable and varies with eye position ( Serrano-Pedraza et al, 2011 ; Wakayama et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the situation is much more complicated in IXT patients, as their visual suppression condition is unstable and varies with eye position ( Serrano-Pedraza et al, 2011 ; Wakayama et al, 2013 ). Patients with IXT can switch the fixating eye spontaneously according to the object position ( Adams et al, 2017 ; Ramachandran and Das, 2020 ). Thus, suppression can change between eyes depending on fixation.…”
Section: Introductionmentioning
confidence: 99%